Experimental Investigations of the Seismic Performance of a Base-Isolated Uninterruptible Power Supply (UPS) through Shaking Table Tests - Gia Toai Truong; Seung-Jae Lee; Ji-Eon Lee; Kyoung-Kyu Choi (Shock and Vibration)
Seismic performance of a UPS through shaking table tests was investigated using the input acceleration time histories with scaling factors of 50%, 100%, and 200%. The first series consists of UPS specimens supported by snip single-corner rectangular pins, and the second series consists of UPS specimens supported by isolator systems. The UPS specimens in the second series significantly reduced the fundamental frequency, peak acceleration, and amplification factors but increased the damping ratio and displacement compared with those of the UPS specimens in the first series. The analytical results obtained from the analytical model agreed well with the experimental results.